2015
DOI: 10.1260/2040-2295.6.4.649
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Wheezing Detection Based on Signal Processing of Spectrogram and Back‐Propagation Neural Network

Abstract: Wheezing is a common clinical symptom in patients with obstructive pulmonary diseases such as asthma. Automatic wheezing detection offers an objective and accurate means for identifying wheezing lung sounds, helping physicians in the diagnosis, long-term auscultation, and analysis of a patient with obstructive pulmonary disease. This paper describes the design of a fast and high-performance wheeze recognition system. A wheezing detection algorithm based on the order truncate average method and a back-propagati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…BPNN was also used by [49] to perform recording classification. The study used 58 recordings with 32 of them containing wheezes obtained using an ECM microphone.…”
Section: Resultsmentioning
confidence: 99%
“…BPNN was also used by [49] to perform recording classification. The study used 58 recordings with 32 of them containing wheezes obtained using an ECM microphone.…”
Section: Resultsmentioning
confidence: 99%
“…Both models enhance the diagnostic abilities of the interpreter who listens and visualizes the respective phonogram, promising easier and more objective acquisition of breath sound teaching skills. 17,[20][21][22] Machine learning models in chest auscultation, when combined with machine learning heart sound models, [21][22][23][24] promise an ease of medical education, implementation of telemedicine, screening of cohorts, diagnosis and medical practice in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…We aim to design our sensor such that it resonates within the frequency range of wheezing in order to achieve the maximum output signal. While the frequency of a wheeze from the trachea lies in the range of 100-2500 Hz, it is reduced to 100-1000 Hz from the chest because lung tissue, chest wall, and skin absorb the higher frequencies before they reach our sensor [5,6]. The chest-wall tissue acts as a low-pass spectral constraint on respiratory sounds, which, when measured on the skin surface with an acoustic sensor (microphone or accelerometer) positioned on human chest, back or neck, typically reside in the frequency band below 1 kHz [26].…”
Section: B Diaphragm Material Size and Shape Selectionmentioning
confidence: 99%
“…A study showed that asthma can be diagnosed at an early stage using non-invasive practices by monitoring the airway resistance in the trachea [4]. This airway resistance produces wheezing characterized by musical, sinusoidal sounds superimposed on breathing with frequencies of 100-1000 Hz and a duration of >250ms [5][6][7][8][9]. Similar to the behavior of sound, wheezing travels through a medium in the form of pressure fluctuations.…”
Section: Introductionmentioning
confidence: 99%